Red flags in detecting credit cooperative fraud: the perceptions of internal auditors - Baú Dal Magro, Cristian; Da Cunha, Paulo Roberto (Review of Business Management, 2017)
Purpose – Red flags are mechanisms that can be used by internal auditors for early detection of possible fraud. In this context, the aim of this study was to identify the relevance credit unions’ internal auditors attribute to red flags in assessing fraud risk. Design/methodology/approach – This article is characterized as descriptive concerning its goals, as a survey as to is procedures, and as quantitative in reference to its approach to the problem. The sample consists of 51 internal auditors working in Credit Union Centers in southern Brazil. Findings – Results indicate that, in the assessment of fraud risk, internal auditors attribute greater importance to red flags referring to operational activities and internal control procedures. In addition, it is suggested that internal auditors are not impartial concerning their perception of relevance of most of the warning signs of the possibility of fraud. Originality/value – The findings contribute by demonstrating to internal auditors the need for greater attention to the use of red flags as auditing tools.